1992
DOI: 10.1139/b92-270
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Lycopersicon species to Bemisia tabaci, a tomato leaf curl virus vector

Abstract: More than 1200 cultivars, breeding lines, and wild species of Lycopersicon were screened for resistance to the tomato leaf curl virus under field conditions. All accessions of Lycopersicon esculentum were found susceptible to tomato leaf curl virus. Three lines of Lycopersicon hirsutum and one of Lycopersicon peruvianum accessions showed apparent resistance to the tomato leaf curl virus owing to the failure of virus transmission by whiteflies. Morphological analysis by light and scanning electron microscopy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
92
1
18

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(114 citation statements)
references
References 13 publications
3
92
1
18
Order By: Relevance
“…In our study, type V trichomes were not subdivided into Va and Vb, and no type VIII trichome, as defined by Channarayappa et al (1992), was identified. The counting of these trichomes may have been hampered by the technique used; it is possible that these trichomes were broken during glass slide preparation.…”
Section: Resultscontrasting
confidence: 51%
See 3 more Smart Citations
“…In our study, type V trichomes were not subdivided into Va and Vb, and no type VIII trichome, as defined by Channarayappa et al (1992), was identified. The counting of these trichomes may have been hampered by the technique used; it is possible that these trichomes were broken during glass slide preparation.…”
Section: Resultscontrasting
confidence: 51%
“…Nonglandular trichomes (II, III and V) are highly similar to each other, differing only in length; out of these, type V is the shortest nonglandular trichome and the most commonly found on tomato leaves. Glandular trichomes (I, IV, VI and VII) have 'heads' that release allelochemicals; of these, only type VI and type VII have multicellular tips (Snyder and Carter, 1985;Channarayappa et al, 1992;Simmons and Gurr, 2005). Because of the great diversity of trichomes found on the leaf surface, some trichomes were subdivided -type V (Va, Vb and Vc) and type VI (VIa, VIb and VIc) -and a new type (VIII) was characterized (Channarayappa et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Os tricomas podem interferir mecanicamente na oviposição, na fi xação e na alimentação de insetos em razão de quatro principais características: densidade, ângulo de inserção, comprimento e tipo (Channarayappa et al 1992).…”
Section: Influência Dos Tipos De Tricomas Foliaresunclassified